Thermal conductivity of solid solutions of Bi₂(Te₁₋ₓSeₓ)₃ (x = 0-0.07) - Martynova, Kateryna; Rogacheva, Olena (Uzhhorod National University, 2022)
Solid solutions Bi₂(Te₁₋ₓSeₓ)₃ are effective materials for an n-leg of thermoelectric cooling devices. Recently, concentration anomalies of properties with a low impurity content were detected in these solid solutions (x ~0.01). It is important to establish whether similar anomalies would be observed on the dependence of thermal conductivity λ from the composition of the solid solution, since λ is one of the parameters that determine the thermoelectric quality factor of the material. Purpose. The purpose of this study was to investigate the concentration dependences of the thermal conductivity of the solid solution of Bi₂(Te₁₋ₓSeₓ)₃ in the interval x = (0-0.07) to identify concentration anomalies and their possible impact on thermoelectric (TE) efficiency. Methodology. Investigation of temperature dependences of thermal conductivity λ was performed by a dynamic calorimeter. Isotherms of λ for different temperatures in the range T = 175-400 K were built on their basis. Results. On isotherms of λ, there is an interval of abnormal growth λ, which becomes more pronounced when the temperature decreases. The presence of this interval is associated with critical phenomena that accompany the transition of the percolation type from dilute to concentrated solid solutions. Conclusions. The estimation of the thermoelectric figure of merit Z of materials is given. It is shown that the detected growth of λ leads to a decrease in Z in the ranges near the critical (x = 0.01), which should be considered in the practical use of solid solutions of Bi₂(Te₁₋ₓSeₓ)₃.
Keywords: thermoelectric materials V₂VI₃; thermal properties; composition; percolation; hermoelectric figure of merit